2022
DOI: 10.2192/ursus-d-21-00009.3
|View full text |Cite
|
Sign up to set email alerts
|

Rub tree use and selection by American black bears and grizzly bears in northern Yellowstone National Park

Abstract: Several of the world's bear species exhibit tree-rubbing behavior, which is thought to be a form of scent-marking communication. Many aspects of this behavior remain unexplored, including differences in rub tree selection between sympatric bear species. We compiled rub tree data collected on Yellowstone National Park's Northern Range (USA) and compared rub tree selection of sympatric American black bears (Ursus americanus) and grizzly bears (U. arctos) at local and landscape scales. During 2017 and 2018, we id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…Brown bears select larger trees, i.e. trees of larger diameter (Clapham et al, bears(Bowersock et al, 2022). Authors have suggested that bears select coniferous over deciduous tree species due to aromatic properties(Clapham et al, 2013;Green and Mattson, 2003;Sato et al, 2014), which might enhance the longevity of the chemical signal(Alberts, 1992).…”
mentioning
confidence: 99%
“…Brown bears select larger trees, i.e. trees of larger diameter (Clapham et al, bears(Bowersock et al, 2022). Authors have suggested that bears select coniferous over deciduous tree species due to aromatic properties(Clapham et al, 2013;Green and Mattson, 2003;Sato et al, 2014), which might enhance the longevity of the chemical signal(Alberts, 1992).…”
mentioning
confidence: 99%